1999
DOI: 10.1128/cmr.12.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Rhinovirus Infections with Asthma

Abstract: SUMMARY Rhinoviruses are the most common cause of the common cold, but they can cause more severe illnesses in people with underlying lung disorders such as asthma, chronic obstructive pulmonary disease, or cystic fibrosis. Epidemiologic studies with sensitive detection methods such as PCR have identified rhinovirus infection as a major source of asthma exacerbations in both children and adults, especially during the spring and fall. Since rhinoviruses cause little tissue destruction, it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 129 publications
2
108
0
6
Order By: Relevance
“…The viral-associated TLRs involved in recognition of nucleic acid motifs, including TLRs 3, 7, 8, and 9, may play a very important role in host defense against viral infection in the tonsils and adenoids [23,25]. For example, since chronic viral infection has been shown to be associated with adenoid hypertrophy and asthma exacerbations, viral-associated TLRs may play a role in the pathogenesis of these diseases [24,26,27]. Previous work with TLR4 has demonstrated that TLR4 tolerance to commensal bacteria may lead to chronic infection and an inflamed tissue state [11].…”
Section: Discussionmentioning
confidence: 98%
“…The viral-associated TLRs involved in recognition of nucleic acid motifs, including TLRs 3, 7, 8, and 9, may play a very important role in host defense against viral infection in the tonsils and adenoids [23,25]. For example, since chronic viral infection has been shown to be associated with adenoid hypertrophy and asthma exacerbations, viral-associated TLRs may play a role in the pathogenesis of these diseases [24,26,27]. Previous work with TLR4 has demonstrated that TLR4 tolerance to commensal bacteria may lead to chronic infection and an inflamed tissue state [11].…”
Section: Discussionmentioning
confidence: 98%
“…For example, IL-1 enhances airway smooth muscle contraction in response to bronchospastic agents and attenuates smooth muscle dilation responses to bronchodilators. 22,23 Differences in immune response, such as the modulation of costimulatory molecules and the induction of antigen presentation, might explain how RV infections cause acute exacerbations in asthmatic patients.…”
Section: How Does Rv Modulate Inflammatory Mediators Of Epithelial Cementioning
confidence: 99%
“…TLR3 may play a very important role in host defense against viral infection in the tonsils. Additionally, since chronic viral infection has been shown to be associated with several conditions in the upper airway, such as asthma exacerbations, the viral-associated TLR3 may play a role in the pathogenesis of disease [30][31][32][33]. TLR3 tolerance due to viral presence in the tonsil may also result in a chronic infection, leading to subsequent tissue damage and development of disease [15].…”
Section: Discussionmentioning
confidence: 97%